Actors and scenarios in the re-formulation of science and technology policy in Nicaragua (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The objective of the article is to show the constellations of actors and their correlations of forces for the construction or reformulation of the Science, Technology and Innovation Policy in Nicaragua. Documentary research and historical analysis have been used applying the qualitative research software MAXQDA. The process of training and design of innovation policy in the country accuses a slow implementation process and empirical learning from innovation initiatives implemented sporadically until 2016 do not feed the new policy formulation. The experiences of innovation hitherto encapsulated in the country require a scaling up and its potential to learn from the sources of innovation in the current state of innovation process in Nicaragua is key to the formation of policies. It has also been found that the country has a conceptual "noise" about innovation, and innovation systems and the actors do not go so far as to establish a concomitant for the construction of Nicaragua's ICT policy and the National Innovation System (NIS). It concludes that the governmental model of creating dialogue, consensus and alliance is an opportunity to be taken by the actors involved.
Keywords: Actors; Innovation; Science and Technology Policies. Innovation System. Scenarios